Full Field and Mean Field Modeling of Grain Growth in a Multiphase Material Under Dry Conditions: Application to Peridotites. Issue 1 (20th January 2020) - Furstoss, Jean; Bernacki, Marc; Petit, Carole; Fausty, Julien; Pino Muñoz, Daniel; Ganino, Clément
Abstract: We present a full field framework based on the level‐set approach, which enables to simulate grain growth in a multiphase material. Our formalism permits to take into account different types of second phases, which can be static or dynamic (i.e., evolving also by grain growth) and reproduce both transient (evolving relative grain sizes) and steady‐state structures. We use previously published annealing experiments of porous olivine or olivine and enstatite mixtures to constrain the parameters of the full field model, and then analyze the results of a peridotite‐like annealing simulation. The experimental grain growth kinetics is very well reproduced while the simulated microstructure morphologies show some differences with experimental ones. We then propose a mean field model calibrated thanks to the full field simulations, which allow us to predict the mean grain size evolution depending on the simplified peridotite composition (e.g., second phase mean grain sizes, fractions). Key Points: A new numerical approach for multiphase grain growth simulation is applied to peridotite analogs A mean field model is calibrated based on the full field simulations We quantify more precisely peridotite grain growth kinetics